All the world - Scanlon, Elizabeth Garton; Frazee, Marla (New York : Beach Lane Books, 2009)
Follows a group of family members and friends through the course of a day as they learn the importance of all things great and small.
Caldecott Medal/Honor
Horn Book Starred
School Library Journal starred
Booklist, July 2009
Bulletin (Center for Children's books), October 2009
Horn Book Starred, September 2009
Keywords: Children's poetry, American; American poetry; American poetry; Picture books for children